PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PT XL AXIATA TBK - Rahmawati, Rahmawati; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of capital structure on profitabilitay at PT XL Axiata Tbk. Capital structure in this study is measured uding Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), while profitability is measured using Return on Assets (ROA) and Return on Equity (ROE). The research method used is a quantitative methodwith descriptive and assosiative approaches. The data used are secondary data obtained from the financial statements of PT XL AXIATA Tbk during the 2018-2023 period. The data analysis techniques include descrptive analysis, multiple linear regression analysis, and classical assumption test consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation test. The results of this study indicate that capital structure has a significant effect on company profitability. A decrease in DER and DAR reflects a reduction in the company’s dependence on debt, which can rduce interest expenses and financial risk. This coundition has a positive impact on incresing profitabiliy, as indicated by the increase in ROA and ROE values. These findingss are consistent with previous studies which state that capital strucure plays an important role in determining company financial performance. Therefore, companies are expected to manage their capital structure optimally to improve profitability and maintain financial stability.